The Devonian–Carboniferous Boundary in western North America: Did tectonic inversion drive Earth system change? - Makram Hedhli; Keith Dewing; Stephen E. Grasby (Earth-Science Reviews, 2026)

Halite formations of Canada for clean energy storage (hydrogen, CAES): A geologic review - Pavel Kabanov; Nicolas Pinet; Frank Brunton; Omid Haeri Ardakani; Christine Deblonde; Keith Dewing; Peter Giles; Paul Durling; Marty Henning; Nicholas Utting (Earth-Science Reviews, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Comparison of optical and geochemical thermal maturity parameters over a stratigraphically controlled natural transect - Dane P. Synnott; Keith Dewing; Omid Haeri Ardakani; Lorenz Schwark; Emma L. Percy; Per Kent Pedersen (Marine and Petroleum Geology, 2023)

A mercury and trace element geochemical record across Oceanic Anoxic Event 1b in Arctic Canada - Jennifer M. Galloway; Stephen E. Grasby; Feiyue Wang; Thomas Hadlari; Keith Dewing; Stéphane Bodin; Hamed Sanei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The diagenetic continuum of steroid hydrocarbon transformation from early diagenesis into the oil window - Dane P. Synnott; Lorenz Schwark; Keith Dewing; Emma L. Percy; Per Kent Pedersen (Geochimica et Cosmochimica Acta, 2023)

Devonian to Carboniferous continental-scale carbonate turnover in Western Laurentia (North America): upwelling or climate cooling? - Makram Hedhli; Keith Dewing; Benoit Beauchamp; Stephen E. Grasby; Rudi Meyer (Facies, 2022)
The Devonian to Carboniferous (DC) transition coincided with a green-to-ice house climatic shift, anoxia, disappearance of lower latitude carbonate banks, and turnover from warm-to-cool water carbonate factories. In western Laurentia, the switch to carbonate factories dominated by cool-water biota was contemporaneous with a tectonically driven palaeogeographic change. To investigate this depositional shift and infer the relative impact of climate vs tectonics, a continental-scale sedimentological and geochemical study was conducted on twelve stratigraphic sections of DC strata from western Canada to southern Nevada (USA). The spatial–temporal distribution of microfacies records the turnover from [i] a Famennian lime mud-rich, shallow warm-water carbonate ramp with low sedimentation rates, mesotrophic conditions and tabular geometry to [ii] Tournaisian to Viséan lime mud-depleted and grainstone dominated cool-water carbonate ramp with anomalous high sedimentation rates, oligotrophic conditions and a pronounced slope. Positive excursions of δ 18 O carb (+ 2‰ V-PDB) and δ 13 C carb (+ 4‰ V-PDB) of Lower Mississippian carbonates likely correspond to the first cooling peak of the Carboniferous-Permian icehouse climate, following carbon withdrawal during black shale deposition during the late Famennian and early Tournaisian. However, late Tournaisian return of photozoan elements and their persistence throughout the Viséan suggests that warmer surface water existed, revealing a decoupling of the lower latitude ocean and the atmosphere. Shoaling of the thermocline was likely a result of cold-water upwelling along an open coast, as the Antler orogen no longer provided an oceanic obstruction to the west. This study shows that carbonate platforms are more susceptible to regional changes than global shifts.